The key drivers in using mobile payment (M-Payment) among student City Campus, Universiti Malaysia Kelantan. - Nurul Farah Umairah Muhammad Rosol; Nur Alyamiza Ismail; Siti Nor Aishah Othman; Liaw Chun Ming (2023)
Nowadays, people tend to use mobile payment transactions more than physical payments. The main objective of this study is to identify the relationship between perceived security, trust, social influence and effort expectancy with behavioural intention to use mobile payment UMK City Campus students. A total 372 of questionnaires were collected. Using SPSS tool containing Descriptive Analysis, Reliability and Validity Test, and Spearman Correlation Analysis, data analysis carried out. The results show the significant correlation between perceived security, trust, social influence and effort expectancy with behavioural intention to use mobile payment. In conclusions, the finding of this study proven that perceived security, trust, social influence and effort expectancy are factor influencing the behavioural intention to use mobile payment among UMK City Campus student. The study has implication for business, financial institutions, government and the individual consumer. With mobile payment, society and consumers can save their time and no longer have to queue up for ATM services and carry cash.